Educación Financiera en los Habitantes de la Parroquia Buenavista, Cantón Chaguarpamba - Condoy Tandazo, Lorgia María (2023)
Financial education is a process aimed at achieving the understanding of basic financial concepts and the development of skills that facilitate optimal decision making within the financial landscape in everyday life. The general objective of this research was to analyze the financial education of the inhabitants of Buenavista parish, Chaguarpamba canton. The study was descriptive, a survey was used as a collection instrument and was adapted to the Programme for International Student Assessment (PISA) Test established by the Organization for Economic Cooperation and Development (OECD), which allows classifying financial knowledge in five levels of respondents. The study population consisted of 168 inhabitants of the Buenavista parish, aged 25 to 44 years old. The results show that the general population has the habit of saving, when buying something they previously consider their ability to pay, they pay their debts within the established term and do not keep a record of their monthly income and expenses; likewise, the general population is within level 3 of the PISA Test, that is, they understand concepts, terms and financial products commonly used in their environment, as well as apply certain basic operations, including the calculation of percentages. Consequently, according to the diagnosis carried out, a financial training program was developed in order to increase and strengthen the financial knowledge of citizens. Finally, the program was implemented and after that, the learning results acquired were evaluated through a questionnaire, thus showing an improvement in the knowledge of the population, placing them in level 5 of the PISA Test. Therefore, it is important to encourage participation in financial education programs to strengthen knowledge and improve financial skills that have an impact on financial wellbeing